Optimalisasi Minat Membaca Melalui Bimbingan dan Konseling - Pristanti, Nindya Ayu (Jurnal Administrasi Pendidikan dan Konseling Pendidikan, 2024)
In the educational context, interest in reading plays an important role in developing students' literacy and academic achievement. This research aims to find out how to encourage interest in reading through guidance and counseling services with an effective approach. This study followed the preferred reporting items for systematic reviews and meta-analyses (PRISMA). Using four databases to search for papers about the study, including: Scholar, researchGate, Science Direct, and Taylor and Francis online. Online search references were found using a procedure that involved typing the keywords “interest in reading” AND “interest in literacy” AND “motivation for reading” for each database. To achieve three articles as a result after the screening procedure, author selection criteria for inclusion and exclusion were applied to the search results of 204 articles generated from the complete database. The conclusion of this review is that to increase interest in reading, it is necessary to implement guidance and counseling services that adopt an appropriate learning approach. Thus, investment in guidance and counseling services that focus on developing interest in reading can make a positive contribution to improving students' overall literacy and academic achievement.